Machado de Assis sob a ótica da crítica mato-grossense, na primeira metade do século XX - Montagner, Iara Sirlene Amorim (2014)
In the present study we address the criticism of Machado de Assis in Mato Grosso based on historiography because we assume that the events of time and space reverberate in the arts, and specifically in Mato Grosso there is no way to separate literature from history. In the first half of the twentieth century, after a violent struggle for power, the majority of the people engaged in the project of construction of the new identity in Mato Grosso were made of writers who used literature as a means of achieving progress and propagate the ideology disseminated by a group of intellectuals led by Dom Aquino Corrêa. Machado de Assis is one of the most studied authors nationwide. The genius of this writer lured many researchers to analyze his works. Observing part of his critical fortune, we examined what there was about him in the literary criticism in Mato Grosso. Thus, we took as a starting point the book Machado de Assis em Mato Grosso – Textos críticos da primeira metade do século XX, authored by Yasmin J. Nadaf, who analyses texts about the creator of Dom Casmurro, written by critics in Mato Grosso. After reading the texts discussed by Nadaf, we set out to analyze how Machado de Assis’s works were received by the best known writers in Mato Grosso in the first half of the twentieth century, comparing this criticism with the one practiced nationwide. During the research we sought a theoretical framework in the historical literature and literary criticism in Mato Grosso and in Brazil from Machado de Assis’s time to the first half of the twentieth century. Therefore, it was possible to classify the critical trend on Machado de Assis, evaluated by critics from that period in Mato Grosso.